Rearing behaviour in the mouse behavioural pattern monitor distinguishes the effects of psychedelics from those of lisuride and TBG - Chen, Yahong; Liu, Junhong; Yao, Yishan; Yan, Haitao; Su, Ruibin (Frontiers in Pharmacology, 2023)
Psychedelics alter consciousness and may have potential for drug development. Given the likelihood that psychedelics are therapeutically active, it is becoming more important to study their effects and mechanisms using preclinical models. Here, we present phenylalkylamine and indoleamine psychedelics on locomotor activity and investigative behavior using the Behavioral Pattern Monitor (BPM). DOM, mescaline, and psilocin reduce locomotor activity at high doses and produce effects on rearings that follow a characteristic inverted U-shaped dose-response function over a range of doses. Pretreatment with the selective 5-HT2A antagonist M100907 reversed the locomotor activity, rearings, and jumps of systemic administration of DOM at low doses (the ascending limb), while holepoking at the full range of doses tested could not be blocked by M100907. Pretreatment with 5-HT2C antagonist SB242084 failed to alter DOM-elicited rearings on the descending limb of the dose-response curve but instead slightly increased locomotor activity occurring at high doses (the descending limb). Hallucinogenic 5-HT2A agonist 25CN-NBOH administration shared striking features common to psychedelics that could be significantly diminished by M100907, whereas nonhallucinogenic 5-HT2A agonist TBG did not affect the locomotor activity, rearings, and jumps in response to its effective doses. The results of these experiments provide strong evidence that DOM-elicited rearing-increasing behavior is a 5-HT2A agonist-mediated effect, with a subsequent decrease in rearing behavior being driven by the inhibition of locomotor activity mediated by the 5-HT2C receptor. Thus, rearing in mice could be utilized to assess psychedelics for 5-HT2A agonist activity and hallucinogen-like behavioral effects.